THE EFFECT OF SERVICE QUALITY AND PRICE ON THE LEVEL OF GUEST SATISFACTION OF PRIME PLAZA HOTEL KUALANAMU - Abdul Mujib; Fahmi Sulaiman (SEAN Institute, 2023)
This study was conducted to see empirically the relationship between service quality and hotel price rates on the level of guest satisfaction staying at Prime Plaza Hotel Kualanamu. Researchers use an associative approach to analyze the influence between variables. The subjects of this study were guests who stayed at Prime Plaza Hotel Kualanamu between June to August 2022. From a total population of 4,368 guests, researchers observed as many as 175 samples of respondents who were previously selected through purposive sampling techniques. The research data was collected by researchers through questionnaire media which was then processed and analyzed to prove the hypothesis. The results of the data analysis show that the quality of service and hotel price rates simultaneously have a positive and significant effect on the level of guest satisfaction of Prime Plaza Hotel Kualanamu. It can be seen from the value of the coefficient of determination (adjusted R2) of 0.951 which if interpreted means 95.10% of guest satisfaction of Prime Plaza Hotel Kualanamu can be explained by the quality of guest service and hotel price rates while the remaining 4.90% is explained by other indicators that are not included in the research variables.